QARAQALPAQ TIL BILIMINDE ANALITIKALÍQ FEYILLERDIŃ QOSPA SÓZ HÁM SÓZ DIZBEKLERINE UQSASLÍǴÍ HÁM ÓZGEShELIKLERI - Mustafaeva, A.J.; Nzamatdinova, D.K. (SCIENCE and SOCIETY, 2026)
This article is studied the features and differences of analytic verbs in the Karakalpak language, similar to compound verbs and phrases. Opinions and discussions are presented on compound verbs in Turkic languages, examples from fiction were cited, analyzed, and clarified on the differences and similarities of compound verbs, analytic verbs, and phrases.